Maestro Carlos Gomes e a República: simbologias e interesses políticos na representação do patrono da música brasileira e herói da pátria. - Santos, Kleiton de Araújo (2020)
Full of symbologies and resignifications, the trajectory of the memory of the composer and conductor Antônio Carlos Gomes after his death in 1896 motivates this research work that focuses on unraveling how the image and representation of this artist had been manipulated and used in the beginning of the Republic. only to create a heroic figure and a Brazilian musical representative, but by reluctantly republicanizing him, they use him to antagonistically legitimate new leaders and a newly created republican symbology. In this sense, the work uses the analytical-descriptive method with the sources, work approaching it through the narratives of the periods that follow, using letters from the composer, articles and articles in newspapers of the time, and also, biographical books and lithographs produced for his honor. This work seeks to understand the reinterpretations made by republicans using these materials and the press coordinated by political groups, understanding how these intertwine with the changes that Brazil was forced to undergo, creating homeland heroes, perfect characters, to motivate a nationalist pride in a cut between 1889 and 1930. These changes guide discourses and generate conflicts in the search to create a unifying Brazilian identity for the nation. To analyze it is to discover other faces of what was built and mobilized in these periods using the memory of an artist, but it is also to unveil the strategies that made it possible for a mestizo to become an example of what it was for the imperial and republican governments to “be a Brazilian”.